2005
DOI: 10.1002/pen.20356
|View full text |Cite
|
Sign up to set email alerts
|

Influence of long-chain branching on the rheological behavior of polyethylene in shear and extensional flow

Abstract: In this work, a study of the influence of molecular structure on the viscoelastic behavior of melts of commercial polyethylene (PE) copolymers, particularly in extensional flows, will be performed. To enable this study to be performed, a series of four very low-density polyethylenes (VLDPEs) (film and blow molding grades) with different parameters of molecular weight (M W ), molecular weight distribution (MWD), and degree of long-chain branching (LCB) will be used. Experiments in shear flow (steady state and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 40 publications
1
19
0
Order By: Relevance
“…[128] However, it has also been found that the PDI has a similar effect on the phase angle δ as the LCB does. [129,130] A unique inflection point or bump (more or less developed) between the minimum and the 90° plateau can be found in long-chain branched polymers. This point shifts to the region having larger |G*| and lower δ in the figure with the increase of LCBD.…”
Section: Van Gurp-palmen Plot (δ(|G*|)mentioning
confidence: 99%
See 1 more Smart Citation
“…[128] However, it has also been found that the PDI has a similar effect on the phase angle δ as the LCB does. [129,130] A unique inflection point or bump (more or less developed) between the minimum and the 90° plateau can be found in long-chain branched polymers. This point shifts to the region having larger |G*| and lower δ in the figure with the increase of LCBD.…”
Section: Van Gurp-palmen Plot (δ(|G*|)mentioning
confidence: 99%
“…Münstedt et al provided excellent work on this topic [152,156,157] among other works. [128,130,158,159] However, the strain hardening in extension can also be a result of very small amount of high-molecular-weight materials in linear polymers. [160,161] The technique is not very sensitive to LCBD either.…”
Section: Extension Rheology (Strain-harding Effect)mentioning
confidence: 99%
“…The LLDPEs differ essentially in terms of degree of long chain branching (LCB) with LLDPE-C being the sample with the highest degree of LCB [29].…”
Section: Materials and Experimental Conditionsmentioning
confidence: 99%
“…1,2 For example, in LDPE extrusion coating process, LCB structure can improve neck-in properties. 1,2 For example, in LDPE extrusion coating process, LCB structure can improve neck-in properties.…”
Section: Introductionmentioning
confidence: 99%
“…To support the polymer design development, a well-defined characterization technique for LCB is required. (1). [6][7][8][9][10] The quantification of LCB of polymer by GPC with triple detectors is commonly based on a LCB frequency (LCBf) calculation with the assumption of the Zimm-Stockmayer (ZS) random branching model.…”
Section: Introductionmentioning
confidence: 99%